Platelet Reduction in Rats Exposed to Chronic Hypoxia Is Associated with Interaction of Glycoprotein Ib Alpha von Willebrand Factor - Wang, Zhuoya; Gomchok, Drolma; Ye, Yi; Wen, Yi; Wuren, Tana (Hämostaseologie, 2025)
Chronic high-altitude hypoxia is associated with reduced platelet count, but it is unclear whether the decrease in platelet count is due to impaired production or increased clearance. This study examines how hypoxia affects platelet production and apoptosis and elucidates the impact of glycoprotein Ibα–von Willebrand factor interaction on platelets in rats using a hypobaric hypoxia chamber. The results showed that the number of megakaryocytes increased under hypoxia; however, the levels of differentiation and polyploidy decreased, while those of apoptosis increased. Platelet production did not reduce according to the reticulated platelet percentage, while platelet apoptosis enhanced; these results suggest that increased platelet clearance was the main reason behind platelet reduction. Our previous microarray results indicated that glycoprotein Ibα (GPIbα) expression increased under hypoxia, which was a protein involved in platelet clearance; therefore, we examined the interaction of platelet GPIbα with the von Willebrand factor (vWF) both in vivo and in vitro to explore the effect of this process on platelets and whether it is related to platelet apoptosis. Under hypoxia, the stronger interaction between GPIbα and vWF promoted platelet apoptosis; inhibiting this interaction reduced platelet apoptosis and increased platelet counts. Platelet reduction is associated with apoptosis induced by the interaction between GPIbα and vWF.
Keywords: apoptosis; glycoprotein Ib alpha; hypoxia; platelet; von Willebrand factor